Pengaruh Sales Promotion dan Service Quality terhadap Keputusan Pembelian pada situs belanja online Zalora - Alya Luthfi (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
This research aims to find out the Effect of Sales Promotion And Service Quality on Zalora Customer Purchasing Decision. The type of research used is associative research with quantitative approaches. by using data collection methods namely Field Research (questionnaire) and Library Research (journal & book). The number of samples used in this study was 100 respondents. The data analysis method used is simple linear regression analysis and t test. The results showed that variables sales promotion (X1) and service quality (X2) had a positive and significant effect on purchasing decision (Y) because the value of tcount > ttable and the significant value was smaller than 0.05 so that Ho was rejected and Ha was accepted. This means that the sales promotion (X1) and service quality (X2) has an effect on purchasing decision (Y).